To determine the average rate of change of a function on a given interval, you can use the formula:
\[ \text{Average Rate of Change} = \frac{f(b) - f(a)}{b - a} \]
where \(f(a)\) is the function value at the beginning of the interval, \(f(b)\) is the function value at the end of the interval, \(a\) is the starting point of the interval, and \(b\) is the endpoint.
In this case, the interval is \(x: [1, 3]\), so we need to find:
- \(f(1)\) (the function value when \(x = 1\))
- \(f(3)\) (the function value when \(x = 3\))
Then plug these values into the formula.
Since I do not have access to the graph and cannot see the specific function values at \(x = 1\) and \(x = 3\), you will need to extract those values from the graph and perform the calculation.
For instance, if \(f(1) = 5\) and \(f(3) = 11\), the calculation would be:
\[ \text{Average Rate of Change} = \frac{11 - 5}{3 - 1} = \frac{6}{2} = 3 \]
Please refer to the graph to find the actual values and compute the average rate of change accordingly. Once you have that computed, you can check which of the provided responses (13, -1, 6, 26) matches your answer.